Local Government Financial Statements Disclosure: A Reflection on Governmental Performance in Central Java, Indonesia - Shinta Permata Sari; Wayan Novitasari (Universitas Muhammadiyah Malang, 2022)
In Indonesia, local government accountability is a reflection of its performance that can be seen from the disclosure of local government financial statements in accordance with Government Regulation (PP) Number 71 of 2010 concerning Government Accounting Standards. Based on the reference and the previous study, the level of adequacy of financial statement disclosure is influenced by several factors: audit findings, legislative size, local government budget expenditure, intergovernmental revenue, and the number of local governments’ agencies. This study analyzes the effect of those factors on the disclosure of local government financial statements in Central Java Provence, Indonesia from 2017 to 2019. This is a quantitative study with secondary data types obtained from Local Government Financial Report Examination Results (LHP LKPD) districts/cities in Central Java Province in 2017 – 2019. The sample consists of 75 local government financial statement disclosure from 34 districts or cities obtained through purposive sampling methods. The analysis method uses multiple linear regression. The result shows audit findings and local government budget expenditure affect the disclosure of local government financial statements. Meanwhile, the legislative size, intergovernmental revenue and number of local governments agencies do not affect the local government financial statements disclosure. This research can be used as an evaluation for local governments in increasing transparency and accountability in their financial management by applicable laws and regulations. This study has limitations that do not describe the overall level of disclosure of local government financial statements, in future research, it is expected to use a longer period and expand the research area.